Elevated circulating levels of GFAP associated with reduced volumes in hippocampal subregions linked to mild cognitive impairment among community-dwelling elderly individuals - Zhang, Ying; Wang, Jun; Zhang, Haibo; Tan, Zhenkun; Zheng, Yingyan; Ping, Junjiao; Zhang, Jie; Luo, Jiali; Li, Linsen; Lu, Liming; Liu, Xinxia (Frontiers in Aging Neuroscience, 2024)
Objective Cerebrospinal fluid biomarkers are challenging to use for diagnosing mild cognitive impairment (MCI) in large populations, and there is an urgent need for new blood biomarkers. The aim of this study is to investigate whether astrocyte activation is correlated with hippocampal atrophy, and to assess the potential of glial fibrillary acidic protein (GFAP) as a biomarker for diagnosing MCI among community-dwelling older individuals. Methods This cross-sectional study included 107 older adults. The levels of GFAP in serum were measured, and the volumetric assessment of gray matter within hippocampal subregions was conducted using Voxel-Based Morphometry (VBM). The relationship between hippocampal subregion volume and blood biomarkers were analyzed using partial correlation. The effectiveness of blood biomarkers in differentiating MCI was assessed using a receiver operating characteristic (ROC) curve. Results We found that serum GFAP levels were significantly elevated in the MCI group compared to the cognitively normal (CN) group. Additionally, individuals with MCI exhibited a reduction gray matter volume in specific hippocampal subregions. Notably, the right dentate gyrus (DG) and right cornu ammonis (CA) subregions were found to be effective for distinguishing MCI patients from CN individuals. Serum levels of GFAP demonstrate a sensitivity of 65.9% and a specificity of 75.6% in differentiating patients with MCI from CN individuals. Conclusion Specific atrophy within hippocampal subregions has been observed in the brains of community-dwelling elderly individuals. Elevated levels of circulating GFAP may serve as a sensitive peripheral biomarker indicative of hippocampal-specific cognitive alterations in patients with MCI.